2012
DOI: 10.1155/2012/585674
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment Elements Involved in the Development of Pancreatic Cancer Tumor

Abstract: Introduction. In spite of intensive research during many years, pancreatic adenocarcinoma remains one of the deadliest cancers. The surgical intervention remains main possibility of treatment because chemotherapy and radiotherapy has a minimal impact on long-term survival. We are still looking for the weak points of this devastating disease. Materials and Methods. Pancreatic tumor tissue samples were collected from 36 patients. Immunohistochemistry staining was used to evaluate expression of growth factors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…In this study, we have shown that high c‐Met expression, assessed with the simplified c‐Met score, is an independent prognostic marker of poor survival in patients with resected stage I–II PDAC. Our results are consistent with previously published data, and show that, with this simple and reproducible scoring method, c‐Met expression is an independent prognostic factor for both DFS and OS in multivariate analysis (Table ) . Discrepancies in the prognostic value of c‐Met expression in PDAC in previous reports could be related to the type of immunoassay method and the use of less discriminant scoring methods for quantifying c‐Met expression.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we have shown that high c‐Met expression, assessed with the simplified c‐Met score, is an independent prognostic marker of poor survival in patients with resected stage I–II PDAC. Our results are consistent with previously published data, and show that, with this simple and reproducible scoring method, c‐Met expression is an independent prognostic factor for both DFS and OS in multivariate analysis (Table ) . Discrepancies in the prognostic value of c‐Met expression in PDAC in previous reports could be related to the type of immunoassay method and the use of less discriminant scoring methods for quantifying c‐Met expression.…”
Section: Discussionsupporting
confidence: 91%
“…Following treatment with 30 µM SU11274, cell motility was suppressed to 1.0±0.3% in MIA-Paca2 cells (P<0.05) and 14.7±3.5% in PK-45H cells (P<0.05) of the level of cells treated with 0 µM SU11274, respectively. Discussion c-Met expression has been identified in pancreatic cancer specimens (11). In the present study, immunostaining detected no c-Met expression at the protein level in normal pancreatic tissues.…”
Section: Su11274 Suppresses Pancreatic Cell Motilitycontrasting
confidence: 52%
“…Consequently, developing therapies for either treating the disease or allowing more patients to qualify for surgery is an area of active research (4,5). High tissue pressure can impede the delivery of therapeutic agents and encourage tumor progression (40,41). Tissue pressure is difficult to measure with currently available invasive pressure catheters.…”
Section: Discussionmentioning
confidence: 99%